(untitled) (Journal of Plant Disease Sciences, 2023)
• Maize (Zea mays L.) is one of the most adaptable developing crops, adapting to a wide range of agro-climatic conditions. Maize is renowned as the “Queen of Cereals” because it has the largest genetic yield potential of any cereal. Several fungal, bacterial, and viral diseases affect it. Among these is Maydis leaf blight, which is caused by the fungus Bipolaris maydis and causes 40-45% yield loss in maize around the world. The current study attempted to investigate the morphological and molecular variance of Bipolaris maydis isolates. B. maydis identification based solely on micro and macroscopic characteristics and morphological characters may result in inaccurate designation. To identify the proper species, we amplified the 18S rRNA gene region by PCR, sequenced it, and compared it to the NCBI data using BLAST. ITS primers were also used for PCR amplification of ITS sections. The amplified product of the 18S rRNA gene was sequenced and the accession numbers were deposited in Gen Bank. In the present study the results obtained from PCR amplification of ITS region with primer pair of ITS1 and ITS4 produced a gene product of 700 bp confirming the isolatesto be Bipolaris maydis.